PENGARUH DIGITAL MANAJEMEN SUMBER DAYA MANUSIA, KEPEMIMPINAN PELAYAN, DAN MOTIVASI KERJA, TERHADAP KINERJA PEGAWAI: STUDI KAUSAL PADA PEGAWAI DINAS KESEHATAN KABUPATEN LEBAK - Ade Jaya Sutisna; Dedeh Kurniasih; Haris Perdana (Universitas La Tansa Mashiro, 2026)
This study aims to analyze the effect of Digital Human Resource Management (Digital HRM), servant leadership, and work motivation on employee performance at the Lebak Regency Health Office. Digital transformation in public sector human resource management is expected to enhance work effectiveness, objectivity in performance appraisal, and the quality of public services. However, empirical evidence indicates that the implementation of digital performance appraisal systems has not yet resulted in optimal improvements in employee performance. Therefore, this study examines psychological and leadership factors as key mechanisms influencing the effectiveness of digital HRM implementation. This research employs a quantitative approach with a causal research design. The population consists of all employees of the Lebak Regency Health Office, with samples selected using proportional sampling techniques. Data were collected through structured questionnaires measuring employees’ perceptions of Digital HRM, servant leadership, work motivation, and employee performance. Data analysis was conducted using path analysis to examine direct effects, indirect effects through work motivation as a mediating variable, and the moderating role of servant leadership in the relationship between Digital HRM and employee performance. The findings are expected to demonstrate that Digital HRM has a positive and significant effect on employee performance, both directly and indirectly through work motivation. Work motivation is anticipated to function as a mediating variable that strengthens the influence of Digital HRM on employee performance. Furthermore, servant leadership is expected to moderate this relationship, indicating that the impact of Digital HRM on employee performance becomes stronger when supported by leadership practices that emphasize service orientation, empowerment, and employee development. The conclusions of this study emphasize that the success of digital human resource management is not solely determined by technological factors but also by employees’ psychological readiness and supportive leadership. Practically, the findings are expected to serve as a foundation for developing human resource policies, strengthening leadership capacity, and optimizing digital performance management systems in local government institutions, particularly within the public health sector